Peningkatan Kemampuan Kosakata Bahasa Inggris Melalui Metode Bercerita Denan Peta Pikiran - Arie Rijanti (Alim | Journal of Islamic Education, 2021)
Improving English Vocabulary Skills Through Storytelling Method With Mind Maps. The action research was conducted at SDN Tugu IX Cimanggis Depok, Thesis, Jakarta, PPS UNJ, 2011. The purpose of this study was to find out: how the learning process is to improve students' English vocabulary skills through the storytelling method with mind maps. This research was conducted at SDN Tugu IX Cimanggis Depok with research subjects as many as 38 second grade students. This research uses action research according to Kemmis and Mc Taggart. The results of the study show that through storytelling activities with mind maps in learning English can improve English vocabulary skills of second grade elementary school students.